A national quality incentive scheme to reduce antibiotic overuse in hospitals: evaluation of perceptions and impact. (28th February 2018) - Islam, J; Ashiru-Oredope, D; Budd, E; Howard, P; Walker, A S; Hopkins, S; Llewelyn, M J
Abstract: Background: In 2016/2017, a financially linked antibiotic prescribing quality improvement initiative Commissioning for Quality and Innovation (AMR-CQUIN) was introduced across acute hospitals in England. This aimed for >1% reductions in DDDs/1000 admissions of total antibiotics, piperacillin/tazobactam and carbapenems compared with 2013/2014 and improved review of empirical antibiotic prescriptions. Objectives: To assess perceptions of staff leading antimicrobial stewardship activity regarding the AMR-CQUIN, the investments made by hospitals to achieve it and how these related to achieving reductions in antibiotic use. Methods: We invited antimicrobial stewardship leads at acute hospitals across England to complete a web-based survey. Antibiotic prescribing data were downloaded from the PHE Antimicrobial Resistance Local Indicators resource. Results: Responses were received from 116/155 (75%) acute hospitals. Owing to yearly increases in antibiotic use, most trusts needed to make >5% reductions in antibiotic consumption to achieve the AMR-CQUIN goal of 1% reduction. Additional funding was made available at 23/113 (20%) trusts and, in 18 (78%), this was <10% of the AMR-CQUIN value. Nationally, the annual trend for increased antibiotic use reversed in 2016/2017. In 2014/2015, year-on-year changes were +3.7% (IQR −0.8%, +8.4%), +9.4% (+0.2%, +19.5%) and +5.8% (−6.2%, +18.2%) for total antibiotics, piperacillin/tazobactam and carbapenems, respectively, and +0.1% (−5.4%, +4.0%), −4.8% (−16.9%, +3.2%) and −8.0% (−20.2%, +4.0%) in 2016/2017. Hospitals where staff believed they could reduce antibiotic use were more likely to do so ( P < 0.001). Conclusions: Introducing the AMR-CQUIN was associated with a reduction in antibiotic use. For individual hospitals, achieving the AMR-CQUIN was associated with favourable perceptions of staff and not availability of funding.